PSYCHOSOCIAL SUPPORT FOR ADOLESCENTS AFFECTED BY POSTDISASTER CONDITIONS THROUGH A TRAUMA HEALING PROGRAM IN BIREUEN REGENCY, ACEH: PENDAMPINGAN PSIKOSOSIAL BAGI REMAJA TERDAMPAK PASCABENCANA MELALUI PROGRAM TRAUMA HEALING DI KABUPATEN BIREUEN, ACEH - Jumiadela Wardiansyah; Mawardiana mawar; Karnilawati (PT. ROCE WISDOM ACEH, 2026)
The disaster that occurred in Bireuen Regency, Aceh, not only caused physical damage but also had a significant psychological impact, especially on adolescents as a vulnerable group. This condition requires psychosocial support efforts to assist the recovery process and improve adolescents' abilities to cope with traumatic experiences after the disaster. This community service activity aims to provide psychosocial support through a trauma healing program for adolescents affected by the post-disaster in Salah Sirong Village, Jeumpa District, Bireuen Regency. The activity was carried out on June 20–21, 2026, using a participatory approach involving the village government, community leaders, parents, and adolescents. The program included psychoeducation, icebreakers, therapeutic games, group counselling, relaxation techniques, and expressive activities to help participants manage their emotions and develop adaptive coping mechanisms. The results of the activity showed that adolescents participated in all series of activities enthusiastically, were better able to express their feelings, increased self-confidence, strengthened social interactions, and had a better understanding of managing disaster-related stress. This program also contributed to increasing the resilience and mental health of adolescents during the post disaster recovery period. Thus, psychosocial support through a trauma healing program is an effective form of intervention in supporting the psychological recovery of adolescents affected by post-disaster and needs to be implemented sustainably through collaboration between universities, government, schools, families, and the community.